Analisa Kekuatan Mekanik Sambungan Las Menggunakan Pola Ayunan Melingkar Dan Zig-Zag Pada Baja Karbon Sedang - Irwan, Irwan; Endriatno, Nanang; Hasanudin, La (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2022)
Welding is one of the metal joining techniques by melting some of the parent metal and filler metal which is currently widely used with different methods and movements of welding electrodes. These methods aim to obtain flat and smooth welds and at the same time become the impetus for the compilers to conduct research entitled "analysis of the mechanical strength of welded joints using circular and zig-zag swing patterns on medium carbon steel" with the aim of knowing the effect of welding patterns on hardness test on medium carbon steel material and the effect of microstructure welding pattern on medium carbon steel material. This research was conducted in August 2020, at the Mechanical Engineering Materials and Technology Laboratory, Department of Mechanical Engineering, Faculty of Engineering, Halu Oleo University Kendari. The tools used are welding machines, grinding machines, welding goggles, pliers, masks and gloves while the materials are 0.5 cm carbon steel plate, welding electrodes, grinding wheels. The results of the first research are that for welding using a circular electrode movement pattern which shows a softer or more ductile result, while for a harder or brittle result, it is shown in the zigzag electrode movement welding process and secondly that the circular electrode movement in the welding process has an impact on the microstructure. in the HAZ area which is getting darker because the structure formed is dominated by pearlite, while in welding the zigzag electrode movement has an impact on the HAZ area which is getting brighter because it is dominated by the bainite structureKeywords: Circular Welding Pattern, Mechanical Strength, Medium Carbon Steel, Zigzag Welding Pattern,